Anti Corruption Attitude Of Students As A Corruption Measure Of Criminal Measures - Yusrianto Kadir (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2018)
This study aims to explain the development of character in changing the legal behavior of students and integrative model of character building in the prevention of corruption. The theoretical approach is directed to two main approaches namely the integration of anti-corruption values ​​and the formation of environments that are not permissive to corruption. The method used through the positivist legal approach and sourced from primary, secondary, and tertiary legal materials. The result of the discussion shows character education should involve not only the aspects of good knowledge (moral knowing), but also feel good or loving good (moral feeling), and good behavior (moral action). The main components forming behavioral intentions are Attitude toward behavior, Subjective norms, Control belief. The expected conclusion of student anti-corruption behavior targeted is the consistency of anti-corruption amid the reality of the external environment. Consistency is expected to further increase into the courage of students to be the vanguard in inviting people to do zero-tolerance against acts of corruption.